Protein, Fiber and Albumin Content of The Formulation of Snakefish Flour (Channa striata) and Cock Flour (Stenochlaena palustris) in Bingka Cake - Octavia, Tera; Handarsari, Erma; Sulistyaningrum, Hersanti; Sya’di, Yunan Kholifatuddin (Yayasan Ahmad Mansyur Nasirah, 2024)
A type of food that is ready to consume known as